The Legal Consideration of Judges in the Crime of Village Fund Corruption: A Case Study of Decision No. 32/Pid.Sus-Tpk/2021/Pn.Pal - Hartanto Hartanto; Juan Sebastian Kusumo Putro (Jurnal Jurisprudence, 2022)
ABSTRACT Purpose of the study: This research aims to analyze the crime of village fund corruption by a Village Head in Criminal Case No. 32/Pid.Sus-TPK/2021/PN.Pal in the legal territory of Palu State Court.  Methodology: This research used the normative juridical method with the statute and case approaches. This was descriptive qualitative research. Results: Results showed that the decision of the state court on the crime of village fund corruption in Criminal Case No. 32/Pid.Sus-TPK/2021/PN.Pal defendant has violated Article 2 clause (1) jo. Article 8 of Law No. 31 of 1999 on the Eradication of the Crime of Corruption as what was amended and added with Law No. 20 of 2001 on the Change of Law No. 31 of 1999 on the Eradication of the Crime of Corruption. The judicial considerations on the sanctions for perpetrators of corrupting village funds are already according to the applicable regulations under the guideline of the Law on Corruption. It was also found that the crime of corruption violated Islamic Sharia. Applications of this study: It is hoped that the results of this paper may answer the issues it analyzed and so that it may become material for consideration in finding accurate and valid resolution guidelines to resolve issues on the crime of village fund corruption in Indonesia. Novelty/Originality of this study: This paper focused on the crime of village fund corruption in Criminal Case No. 32/Pid.Sus-TPK/2021/PN.Pal and it was added with the perspective of Islamic values. Keywords: Village fund, corruption, judicial consideration, Islamic values